Pterostilbene Attenuates Particulate Matter-Induced Oxidative Stress, Inflammation and Aging in Keratinocytes - Wei-Lin Teng; Pao-Hsien Huang; Hui-Chun Wang; Chih-Hua Tseng; Feng-Lin Yen (MDPI AG, 2021)
Particulate matter (PM) is the main indicator of air pollutants, and it may increase the level of reactive oxygen species (ROS) in keratinocytes, leading to skin inflammation, aging, and decreased moisturizing ability. Pterostilbene (PTS) is a dimethylated analog of resveratrol that has antioxidant effects. However, the molecular mechanisms of PTS in preventing PM-induced keratinocyte inflammation and aging have not been investigated yet. Therefore, we used PM-induced human keratinocytes to investigate the protective mechanisms of PTS. The results showed that 20 μM PTS had no toxicity to HaCaT keratinocytes and significantly reduced PM-induced intracellular ROS production. In addition, nuclear translocation of the aryl hydrocarbon receptor (AHR) was inhibited by PTS, leading to reduced expression of its downstream CYP1A1. PTS further inhibited PM-induced MAPKs, inflammation (COX-2), and aging (MMP-9) protein cascades, and rescued moisturizing (AQP-3) protein expression. We analyzed the PTS content in cells at different time points and compared the concentration required for PTS to inhibit the target proteins. Finally, we used the skin penetration assay to show that the PTS essence mainly exists in the epidermal layer and did not enter the system circulation. In conclusion, PTS could protect HaCaT keratinocytes from PM-induced damage and has the potential to become a cosmetic ingredient.